2001
DOI: 10.1126/science.1061692
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Neutralizing Human IgG Against HIV-1: A Template for Vaccine Design

Abstract: We present the crystal structure at 2.7 angstrom resolution of the human antibody IgG1 b12. Antibody b12 recognizes the CD4-binding site of human immunodeficiency virus-1 (HIV-1) gp120 and is one of only two known antibodies against gp120 capable of broad and potent neutralization of primary HIV-1 isolates. A key feature of the antibody-combining site is the protruding, finger-like long CDR H3 that can penetrate the recessed CD4-binding site of gp120. A docking model of b12 and gp120 reveals severe structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
745
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 849 publications
(783 citation statements)
references
References 37 publications
25
745
2
7
Order By: Relevance
“…1998), 1HZH (Saphire et al. 2001) for investigating both antibody–antigen interactions and antibody–receptor interactions. In particular, here we investigated the influence of the glycosylation/fucosylation on the interactions between the Fc γ RIIIA and the Fc fragments within the two in‐house developed chimera mAb models Chimera 1A and Chimera 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1998), 1HZH (Saphire et al. 2001) for investigating both antibody–antigen interactions and antibody–receptor interactions. In particular, here we investigated the influence of the glycosylation/fucosylation on the interactions between the Fc γ RIIIA and the Fc fragments within the two in‐house developed chimera mAb models Chimera 1A and Chimera 2 .…”
Section: Discussionmentioning
confidence: 99%
“…1998), and 1HZH (Saphire et al. 2001) and of several mAb fragments in complex with their interactors, that is, a human IgG1–Fc fragment in complex with its receptor, Fc γ RIII (see 3SGJ, 3SGK) (Sondermann et al. 2000), and the infliximab Fab fragment in complex with TNF α (see 4G3Y) (Liang et al.…”
Section: Introductionmentioning
confidence: 99%
“…This hydrodynamic size is in accordance with the value predicted by using the Hydropro software 53 on the crystal structure of an intact IgG1 mAb (PDB ID 1hzh). 54 Refractive index, refractive index increment, and viscosity…”
Section: Static and Dynamic Light Scatteringmentioning
confidence: 99%
“…[9,107] From the neutralizing antibody IgG b12, a peptide domain known as CDR H3 was identified to be involved in binding to the gp120 on HIV-1 and thereby blocking the interaction with CD4 receptor on the host cell and causing neutralization of the virus. [108] Using a consecutive ester-amide/thiol-ene postpolymerization modification strategy, [109] a library of polymer conjugates was prepared that presented multiple copies of the CDR H3 peptide via thioether side chains (35). HIV-1 inhibitory properties with HIV-1 HXB2 on HOS CCR5 cells revealed that midsized polymer conjugates displayed the highest antiviral efficacy (IC 50 ¼ 2-3 Â 10 À6 M total peptide content) while lower efficacies were determined for the copolymers with high and low molecular weight (IC 50 % 10 Â 10 À6 M total peptide content).…”
Section: Polymer Conjugated Entry and Fusion Inhibitorsmentioning
confidence: 99%